Microstructural white matter tract alteration in Prader‐Willi syndrome: A diffusion tensor imaging study. Issue 3 (23rd August 2017) - Rice, Lauren J.; Lagopoulos, Jim; Brammer, Michael; Einfeld, Stewart L.
Abstract : Prader‐Willi Syndrome (PWS) is a genetic disorder characterized by infantile hypotonia, hyperphagia, hypogonadism, growth hormone deficiency, intellectual disability, and severe emotional and behavioral problems. The brain mechanisms that underpin these disturbances are unknown. Diffusion tensor imaging (DTI) enables in vivo investigation of the microstructural integrity of white matter pathways. To date, only one study has used DTI to examine white matter alterations in PWS. However, that study used selected regions of interest, rather than a whole brain analysis. In the present study, we used diffusion tensor and magnetic resonance (T 1‐weighted) imaging to examine microstructural white matter changes in 15 individuals with PWS (17–30 years) and 15 age‐and‐gender‐matched controls. Whole‐brain voxel‐wise statistical analysis of FA was carried out using tract‐based spatial statistics (TBSS). Significantly decreased fractional anisotropy was found localized to the left hemisphere in individuals with PWS within the splenium of the corpus callosum, the internal capsule including the posterior thalamic radiation and the inferior frontal occipital fasciculus (IFOF). Reduced integrity of these white matter pathways in individuals with PWS may relate to orientating attention, emotion recognition, semantic processing, and sensorimotor dysfunction.